2018
DOI: 10.1104/pp.17.00925
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokinin Oxidase/Dehydrogenase CKX1 Is a Membrane-Bound Protein Requiring Homooligomerization in the Endoplasmic Reticulum for Its Cellular Activity

Abstract: Degradation of the plant hormone cytokinin is controlled by cytokinin oxidase/dehydrogenase (CKX) enzymes. The molecular and cellular behavior of these proteins is still largely unknown. In this study, we show that CKX1 is a type II single-pass membrane protein that localizes predominantly to the endoplasmic reticulum (ER) in Arabidopsis (). This indicates that this CKX isoform is a bona fide ER protein directly controlling the cytokinin, which triggers the signaling from the ER. By using various approaches, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 98 publications
(143 reference statements)
1
49
0
1
Order By: Relevance
“…In addition, ancient and non-ancient CKXs present differential subcellular localizations (Table 1). Studies on AtCKXs have revealed that the ancient AtCKX7 uniquely localizes to the cytosol, whereas the non-ancient AtCKXs predominantly localize to the endoplasmic reticulum (ER), vacuole or apoplast 11,13,40 . This discrepancy in subcellular localizations between ancient and non-ancient CKXs is likely related to their respective housekeeping and regulatory roles in angiosperms.…”
Section: Evolution Of Ckx Genes In Angiospermsmentioning
confidence: 99%
“…In addition, ancient and non-ancient CKXs present differential subcellular localizations (Table 1). Studies on AtCKXs have revealed that the ancient AtCKX7 uniquely localizes to the cytosol, whereas the non-ancient AtCKXs predominantly localize to the endoplasmic reticulum (ER), vacuole or apoplast 11,13,40 . This discrepancy in subcellular localizations between ancient and non-ancient CKXs is likely related to their respective housekeeping and regulatory roles in angiosperms.…”
Section: Evolution Of Ckx Genes In Angiospermsmentioning
confidence: 99%
“…The two CKX gene products, CKX1 and CKX2, differ in their subcellular localization and biochemical characteristics. A tagged CKX1 protein was shown to localize predominantly to the endoplasmic reticulum (Niemann et al, 2018), while a CKX2-GFP fusion protein localized to the endoplasmic reticulum and possibly also to the apoplastic space Zürcher et al, 2016). Furthermore, the CKX1 protein preferred CK ribosides and N 9 -glucosides as substrates, while N 6 -isopentenyladenine (iP) and iP riboside were preferred by CKX2 (Galuszka et al, 2007).…”
Section: Generation Of Transgenic Barley Plants With Increased Ckx Acmentioning
confidence: 99%
“…It seems that the main site of CK inactivation is localized in the apoplast by CKX2 and CKX4-6 [ 151 ]. CKX1 and 3 were initially predicted as mitochondrial based on in silico experiments [ 152 ], although later GFP fusions showed that these two enzymes are predominantly targeted to vacuole, with some observed signal also in ER [ 151 ] where they are catalytically active [ 153 ]. In the case of CKX7, the lack of a signal peptide suggests that it is localized to the cytosol [ 154 ] ( Figure 3 ).…”
Section: Cytokininsmentioning
confidence: 99%